2021
DOI: 10.1109/access.2021.3131733
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of AI-Based Facial Emotion Recognition: Features, ML & DL Techniques, Age-Wise Datasets and Future Directions

Abstract: Facial expressions are mirrors of human thoughts and feelings. It provides a wealth of social cues to the viewer, including the focus of attention, intention, motivation, and emotion. It is regarded as a potent tool of silent communication. Analysis of these expressions gives a significantly more profound insight into human behavior. AI-based Facial Expression Recognition (FER) has become one of the crucial research topics in recent years, with applications in dynamic analysis, pattern recognition, interperson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 176 publications
0
22
0
Order By: Relevance
“…Now, although there have been different implementations carried out on kids’ emotion dataset, it was also observed that there is a scarcity of such dataset as there are not as many datasets of kids as compared with adults, which is indicated in a latest study [ 1 ]. It is also observed that, although the datasets of kids’ emotion are few, the individual quantity is less but the emotions recorded are also different as shown in Table 2 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Now, although there have been different implementations carried out on kids’ emotion dataset, it was also observed that there is a scarcity of such dataset as there are not as many datasets of kids as compared with adults, which is indicated in a latest study [ 1 ]. It is also observed that, although the datasets of kids’ emotion are few, the individual quantity is less but the emotions recorded are also different as shown in Table 2 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…After the literature review, the authors observed a scarcity in kids’ emotion datasets and saw that most of these datasets have not even achieved more than 75% accuracy after applying various approaches based on a latest study [ 1 ]. To challenge this, the authors created their own dataset and used the LIRIS dataset as well, and they also created separate versions of the datasets called LIRIS-Mesh and Authors-Mesh by using 3D landmark points, which were later experimented with various deep CNN models; the authors performed a comparative analysis of all the dataset types using the wide array of CNNs used.…”
Section: Proposed Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In [ 31 ], the different stages of Facial Emotion Recognition (FER) such as pre-processing, feature extraction and classification using various methods and state-of-the-art CNN models are discussed. Comparison between different deep learning models, their benchmark accuracy and their architectural details are also discussed for model selection based on application and dataset.…”
Section: Introductionmentioning
confidence: 99%